Vacuum consolidation and soil-water characteristic curves of clay - Lee, Ken Wei (Nanyang Technological University, 2022)
The objectives of this study are to investigate the influence of vacuum consolidation on undrained shear strength of fine-grained soil and its soil-water characteristic curve (SWCC), as well as investigate the strength improvement differences between surcharge preloading and vacuum preloading. Kaolin was used and first made into a slurry with the addition of water. The slurry was subjected to different pre-consolidation pressures in a consolidation tank to simulate surcharge preloading. Consolidated kaolin samples were trimmed into cylindrical specimens that measured a diameter of 38 mm and a height of 76 mm. To determine the SWCC, several specimens were placed in the pressure plate device and subjected to various matric suctions. The undrained shear strength of the soil specimens was determined using unconfined compression (UC) test.